Relationship of adiponectin and leptin with autoimmunity in children with new‐onset type 1 diabetes: a pilot study. Issue 4 (5th March 2015) - Hecht Baldauff, Natalie; Tfayli, Hala; Dong, Wenxiu; Arena, Vincent C; Gurtunca, Nursen; Pietropaolo, Massimo; Becker, Dorothy J; Libman, Ingrid M
Abstract : Aim: To explore racial differences in adiponectin, and leptin and their relationship with islet autoimmunity in children with new‐onset type 1 diabetes (T1D). Methods: Medical records were reviewed from a cohort of new‐onset clinically diagnosed T1D subjects matched by race, age, gender, and year of diagnosis. Sera were available for 156 subjects (77 African American (AA), 79 Caucasian (C), 48% male, age of 11.1 ± 3.8 yr) and assayed for adiponectin and leptin prior to (D0), 3, 5 d, and 2–4 months (M3) after insulin therapy and islet autoantibodies to GAD, IA2, insulin, and ICA were measured at onset. Results: Adiponectin levels increased significantly following insulin therapy by day 5 (D5) (D0: 13.7 ± 7.2 vs. D5: 21.3 ± 9.9 µg/mL, p < 0.0001), but no further significant increase from D5 to M3. At DO, AA had lower adiponectin levels (10.5 vs. 15.7 µg/mL, p = 0.01), were more often overweight than C (55 vs. 18%, BMI ≥ 85th‰) and fewer had positive autoantibodies (72 vs. 87%, p = 0.05). Racial differences in adipocytokines disappeared after adjustment for BMI. At M3, subjects with more number of positive autoantibodies had higher adiponectin levels (p = 0.043) and adiponectin/leptin ratio (ALR) (p = 0.01), and lower leptin levels (p = 0.016). Conclusion: Adiponectin levels increased acutely with insulin therapy. Significantly lower adiponectin levels in AA were related to greater adiposity and not race. These pilot data showing those with the fewest autoantibodies had the lowest adiponectin levels, supporting the concept that insulin‐resistant subjects may present with clinical T1D at earlier stages of β‐cell damage.